Accelerating Graduate Employability through Work-Integrated Learning - Mabungela, Mvuyisi; Mtiki, Victor (Research in Social Sciences and Technology, 2024)
Work integrated learning (WIL) encompasses educational experiences that merge academic knowledge and practical application in a professional setting, benefiting both students and the existing workforce. The objective of incorporating WIL into education is to foster the integration of theoretical understanding by engaging students in a combination of academic coursework and hands-on work-related activities. With the rise in unemployment, WIL appears to help organizations to get graduates that have all the attributes and skills relevant in the world or work, thereby expanding and growing their businesses ensuring greater prosperity for all concerned. The aim of this article was to assess the role Work Integrated Learning in accelerating Graduate Employability. Four WIL coordinators from different academic programmes that offer WIL as a module participated in this paper. Data was analysed using Thematic analysis, following Braun & Clark steps. The study revealed a direct correlation between academic performance and practical application in the professional setting. This paper therefore argues that WIL programmes can contribute immensely to the overall development of graduates and increase their chances of employment. The study revealed that WIL coordinators should review placement arrangements to improve WIL. This study found that Work Integrated Learning (WIL) has a positive effect on graduate employability and skills development, and that university WIL coordinators should review placement arrangements to ensure that students have enough training and development prior to placement.